Quantum probe hyperpolarisation of molecular nuclear spins - David A. Broadway (Nature Portfolio, 2018)
Molecules with ‘hyperpolarised’ nuclear spins can be used to improve MRI performance but require an efficient polarisation method. Broadway et al. demonstrate a quantum control protocol using a nitrogen vacancy centre inside a diamond to hyperpolarise protons within molecules deposited on the surface.